2023
DOI: 10.1007/s10840-022-01417-4
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide survey on implantation of and outcomes for conduction system pacing with His bundle and left bundle branch area pacing leads

Abstract: Background Adoption and outcomes for conduction system pacing (CSP), which includes His bundle pacing (HBP) or left bundle branch area pacing (LBBAP), in real-world settings are incompletely understood. We sought to describe real-world adoption of CSP lead implantation and subsequent outcomes. Methods We performed an online cross-sectional survey on the implantation and outcomes associated with CSP, between November 15, 2020, and February 15, 2021. We described survey responses and reported HBP and LBBAP outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“… 2 Conduction system pacing including His bundle pacing (HBP) and left bundle branch area pacing (LBBAP) has emerged as an alternative pacing strategy to prevent or mitigate systolic heart failure. 3 The purpose of our study was to compare the performance of leads in RV, HB, and LBBA positions in a real-world cohort.…”
mentioning
confidence: 99%
“… 2 Conduction system pacing including His bundle pacing (HBP) and left bundle branch area pacing (LBBAP) has emerged as an alternative pacing strategy to prevent or mitigate systolic heart failure. 3 The purpose of our study was to compare the performance of leads in RV, HB, and LBBA positions in a real-world cohort.…”
mentioning
confidence: 99%
“…Conduction system pacing (CSP), including His bundle pacing (HBP), is an emerging technique for preventing pacing-related adverse effects [ 4 ] and is included in European Society of Cardiology guidelines on cardiac pacing and cardiac resynchronization therapy (CRT) [ 5 ]. CSP, initially preferred, is considered safe and suitable in most patients with an indication for pacemaker implantation [ 2 , 6 ]; however, it still has not become the first-choice method of pacing [ 7 ]. Studies confirmed HBP’s feasibility, favorable safety profile, and clinical benefits compared with RVP [ 1 , 2 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Two cardiac pacing techniques have been implemented in routine clinical practice with the aim of capturing either the His bundle or the left bundle branch and, consequently, using the intrinsic conduction system for ventricular electrical activation. Left bundle branch area pacing (LBBAP) has gradually become the preferred option for physiological pacing in many laboratories due to a wider target area and better pacing and sensing thresholds compared with His bundle pacing [ 2 ]. Moreover, compared with conventional RVP, several studies have shown a net clinical benefit of LBBAP in terms of ejection fraction preservation and reduced hospitalizations for heart failure [ 3 ].…”
Section: Introductionmentioning
confidence: 99%